The wind in the willows - Grahame, Kenneth (London : Usborne, 2005)
The classic story retold for children growing in reading confidence. Mole, Ratty, Badger and the infamous Mr Toad love nothing more than messing around on the river. But when Mr Toad develops an obsession with motor vehicles, will his friends be able to help before he loses everything?
Keywords: Children's fiction